Orbital Atherectomy Prior to Drug-Coated Balloon Angioplasty in Calcified Infrapopliteal Lesions: A Randomized, Multicenter Pilot Study. (December 2022) - Zeller, Thomas; Giannopoulos, Stefanos; Brodmann, Marianne; Werner, Martin; Andrassy, Martin; Schmidt, Andrej; Blessing, Erwin; Tepe, Gunnar; Armstrong, Ehrin J.
Purpose: Optimal balloon angioplasty for infrapopliteal lesions is often limited by severe calcification, which has been associated with decreased procedural success and lower long-term patency. Materials and Methods: This was a prospective, randomized, multicenter pilot trial that included adult subjects with calcified lesions located from the popliteal segment below the knee (BTK) joint to within 5 cm above the ankle with ≥70% diameter stenosis by angiography. Patients were randomized 1:1 to undergo orbital atherectomy (OA) with adjunctive drug-coated balloon (DCB) angioplasty versus plain balloon angioplasty (BA) and DCB angioplasty (control). The periprocedural and 12 month outcomes of both procedures were compared. Results: Overall, 66 subjects (OA + DCB = 32 vs control = 34) were included in an intention to treat analysis. Baseline demographics and lesion characteristics were well-balanced. The mean lesion length was 101.3 mm (SD = 72.8 mm) and 78.8 (SD = 61.0 mm) in the OA + DCB and control groups, respectively, with almost all lesions having severe calcification per the Peripheral Academic Research Consortium (PARC) criteria. Chronic total occlusions (CTOs) were present in 43.8% and 35.3% of the patients in the OA + DCB and control groups, respectively. The technical success of OA + DCB versus DCB was 81.8% and 89.2%, respectively, with 3 slow flow/no reflow, 1 perforation, 1 severe dissection occurred in OA + DCB group, and one distal embolization occurred in the control group. The target lesion primary patency rate was numerically higher in the OA + DCB versus control group at 6 (88.2% vs 50.0%, p=0.065) and 12 month follow-up (88.2% vs 54.5%, p=0.076). The 12 month freedom from major adverse events, clinically-driven target lesion revascularization, major amputation, and all-cause mortality rates were similar between both groups. Conclusion: The results of the Orbital Vessel PreparaTIon to MaximIZe Dcb Efficacy in Calcified BTK (OPTIMIZE BTK) pilot study indicated that utilization of OA + DCB is safe for infrapopliteal disease. Further prospective adequately powered studies should investigate the potential benefit of combined OA + DCB for BTK lesions.